I förfallet speglas staden - Bratel, Johanna (2008)
The Essay starts with studying the time after the Second World War and its boom, the force behind many of the abandoned locations we see in our city today. Thereafter the idea of place is looked into, its importance for the individual and how the own individual experience affects the experience of place. It is about how we can create own places and through that recapture the city and give it meaning and contents again. The social aspects are being discussed as an important component of creating a feeling of reality. Further studies the abandoned rooms historical values since the past have an ability to raise the experience of a place. How decayed depends highly of economy and how we have gotten so used to changes that we accept capitalism as a driving force to decay is also being discussed. Thereafter the planers roll for the abandoned places in the city is being raised. What make the city an exciting place are all the countless meetings and conflicts it creates. That is also what makes the planers work so difficult. The planning process is about creating boundaries; the modern city is afraid of conflicts and creates boundaries with distance. The planner wishes for initiative and creativity to the places he create, however that easily disappear when the loose boundaries get tighten up. Planning is about creating beautiful places; the question is from whose point of view. Further different ways of exploring the abandoned room with focus on the experience is being studied. The first one is urban exploring, which is about seeking, exploring and really experience the abandoned room. The meaning for the individual with doing this is also being highlighted. Thereafter is a study of the Situationists, an artistic movement created during the 60s. It criticized the western spectacle-society and strived towards a new one where the fantasy ruled. They experienced the urban environment with a systematically stray. Inspired of the Situationists were the, originally Italian, Stalker-collective that practices a critical form of walking, transurbance. They see the places the city has chosen not to. Stalker believes that this is room that should not be filled with objects but with meaning. That leads me to my own exploration of the abandoned room. I do this by following the manifest of Stalker; my result is pictures and notes. Finally a discussion about the work material that has been processed is being held.